Terminological Difficulties in Dene Language Interpretation and Translation - Harnum, Betty (Meta, 1993)
AbstractIn thé Northwest Territories, there are daily demands for interpreting and translating in all the Dene languages. The people who perform this role rarely have the opportunity to specialize in any specific field, so they must try to develop an understanding of as many subjects as they can. This paper highlights some of the inter-lingual difficulties faced by the interpreters, along with a brief explanation of the methods used to develop new terminology in the Dene languages. It is demonstrated that the methods used in Dene language terminology development are the same as those used in other languages.